ANALISIS PENINGKATAN JALAN AKIBAT KERUSAKAN STRUKTUR PERKERASAN DI ATAS TANAH EKSPANSIF - Chasanah, Faizul (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2015)
Performance of pavement structure related to the material and subgrade conditions. This research was conducted to evaluate the damage to the flexible pavement, to analyze the influence of potential and expansive pressure of subgrade, and to analyze pavement thickness of flexible pavement and rigid pavement that has been done by the government in 2012.The location for this research is the road from Purwodadi to Geyer and from km 66+650 to km 87+180. The analysis done with evaluate of the road damage was based on secondary data from Bina Marga department and observation in the field. The early research with taking some soil sample and then testing in laboratory to determine the swelling potentials and swelling pressure by Seed (1962) method. While, the analysis of pavement thickness was designed using the AASHTO (1993) and Bina Marga method. The result of research show the existing condition have ten locations with severely damaged and one location with moderately damaged. Based on the laboratory tests results, the soil condition has a critical expansive degree and high expansive pressure. The average value of expansive degree to all sample show > 10 % and > 300 kPa for expansive pressure. The analysis using AASTHO (1993) method generated additional pavement thickness of 18.5 cm which was required on flexible pavement while the analysis by Bina Marga method produced the required pavement thickness of 23 cm on rigid pavement. Therefore, it can be concluded that overlay in the Purwodadi - Geyer road was not able to serve the traffic based on service life of ten years.